Management of special patient groups with hepatitis B virus infection: The EASL 2017 Clinical Practice Guidelines - Idilman, Ramazan (Turkish Journal of Gastroenterology, 2017)
Abstract The morbidity and mortality of hepatitis B virus-related liver disease are linked to the persistence of the hepatitis B virus replication. Viral suppression with antiviral therapy has been shown to provide clinical benefits. Several special groups of patients with hepatitis B virus infection require special attention. In this brief report, based on European Association for the Study of the Liver 2017 Clinical Practice Guidelines on the management of hepatitis B virus infection, the current optimal management of special patient groups with hepatitis B virus infection is summarized. Cite this article as: Idilman R. Management of special patient groups with hepatitis B virus infection: The EASL 2017 Clinical Practice Guidelines. Turk J Gastroenterol 2017; 28: 518-21.